Motor fitness of young children undergoing general development exercises - Joanna Harasimowicz; Paweł Harasimowicz; Agata Wawryków; Katarzyna Korabiusz; Monika Stecko (Kazimierz Wielki University, 2019)
Objectives : A still small number of Poles declare regular physical activity. International Obesity reports Task Force shows that 30-45 million children in the world aged 5 to 17 suffer from overweight, and under the age of five, 22 million. In total, nearly 155 million children and adolescents are obese or overweight. Currently in Poland is the highest percentage of men over 15 years of age suffering from these conditions among all European Union countries. The research aims to assess the impact of general conditioning exercises on the development of motor fitness of pre-school children. Material and methods : The research was carried out in 2013 at the kindergarten in Szczecin. The children who took part in the study were aged three to six years. Classes were conducted according to the "Key to Learning" program, which was based on the ideas of LeoVygotsky . The study involved 82 preschoolers, including 38 girls and 44 boys. Results : Compiled results indicate that physical activity determines the proper formation of traits not only motor but also psychological and social behavior in pre-school children. Own research has shown that general development exercises positively influence the level of children's physical fitness, they show on average a very good and good level, which should positively affect their health. Conclusions : Physical efficiency is one of the most important health parameters, and its high level obtained in the early years guarantees correct adaptation in later periods of life. In children and adolescents, the right amount of traffic plays a huge role. Encouraging and introducing as early as possible an active form of spending time both in kindergarten and outside it is very important and positively affects motor efficiency of children. kay words : motor fitness, health, physical activity, general development exercises, sport, children